Speaker Verification Based Fractal Geometry - George, Loay; Al-Ani, Laith; Mahdi, Mohammed (Iraqi Journal of Science, 2025)
The research shows that the fractal structure of the speech signal exhibitsfractal characteristics. The encouraging analysis results indicated that the fractaldimension have good discrimination capabilities for speech signal, where it gavea speaker recognition percentage about 70% (In the field of research for a singleparameter this percentage be valued), and these capabilities are strongly dependson the setting situations of the recording process. The pitch period is the anotherused parameter supported to the fractal dimension to strengthen the verificationdecision. Where the pitch period estimated by a new suggested simple method togave a speaker verification percentage about 90%. The coalition work of the twoparameters (fractal dimension and pitch period) gave a speaker verificationpercentage of about 85%.